Access to vaccination among refugees, asylum seekers and internally displaced persons in Sub-Saharan Africa: a systematic review - Nsikakabasi Samuel George; Archibong Edem Bassey; Jeny Alejandra Aguilera Cruz; Marzena Tambor (Discover Public Health)
Abstract Aim This review aimed to synthesize scientific evidence on the access to vaccination among refugees, asylum seekers, and internally displaced persons (IDPs) in Sub-Saharan Africa (SSA). Method This systematic review was conducted in accordance with the PRISMA guidelines. PubMed, Embase, Web of Science, Scopus, and CINAHL were searched for studies published between 2014 and 2024. Eligible publications were limited to studies in English language in peer-reviewed journals. Vaccination coverage, as well as barriers and facilitators to access vaccination for refugees, asylum seekers, and IDPs in SSA were considered as outcomes of interest. Results A total of 30 studies were included in the review, covering vaccines for 13 infectious diseases in 10 countries in SSA. Vaccine coverage and uptake varied and ranged from 26.2% for BCG to over 100% for meningitis vaccine. However, high dropout rates were reported for all vaccines indicating low uptake. Identified individual and systemic barriers were vaccine hesitancies and low awareness, competing priorities, busy schedule and absence, family and community influences, vaccine unavailability and stockouts, insecurity due to ongoing conflict, logistics and storage constraints, and long distances to health facilities. Facilitators included positive attitude towards vaccines, social mobilization and community engagement, leverage on existing structures, and clear vaccination policies. Conclusion This review shows varying vaccine coverage and low access, while underscoring the importance of multifaceted strategies to address existing challenges in ensuring more equitable vaccine access.